ANALYSIS OF RELIABILITY OF RESERVED AUTOMATIC CONTROL SYSTEMS OF INDUSTRIAL POWER PROCESSES - V. A. Anishchenko; E. L. Myslo; A. N. Ivanova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2014)
This paper describes the comparative analysis of the main structural schemes for reserved automatic control and regulation devices of important objects of power supply with increased reliability requirements. There were analyzed schemes of passive and active doubling with control device, passive and active tripling, combined redundancy and majority redundancy according to schemes: “two from three” and “three from five”. On the results of calculations fulfilled there was made comparison of these schemes for ideal devices of built-in control and ideal majority elements. Scales of preferences of systems according to criterion of average time maximum and average probability of no-failure operation were built. These scales have variable character, depending on intervals in which there is a parameter obtained by multiplication of failure rate and time. The sequence of systems’ preferences is changing and is depending on each system failures and in moments of curves crossing of average probability of no-failure operation of systems. Analysis of calculation results showed the advantages of tripling systems and combined redundancy in reliability and this is achieved by a great amount of expenses for these systems creation. Under definite conditions the reliability of system of passive tripling is higher compared to system of active doubling. The majority schemes allow determining not only the full but also single (metrological) failures. Boundary value of unreliability of built-in control device is determined, and this allows making a perfect choice between systems of active and passive redundancy.